The Influence of Ecoprint Activities with Belida Fish Pattern from South Sumatra on the Fine Motor Development of Children Aged 5–6 Years - Fitriani, Ira; Suryani, Yuni Dwi (Journal of English Language and Education, 2025)
As the field of early childhood education continues to evolve, various innovative learning methods have been implemented to support the development of children's fine motor skills. One method that has gained attention is ecoprint activities, which are known to enhance motor skills through artistic and creative engagement. This study aims to examine the effect of Ecoprint activities featuring the Belida fish pattern, a cultural symbol of South Sumatra, on the fine motor development of children aged 5–6 years at RA Jamiyatul Qurro KH. Burlian, Ogan Komering Ulu. The research employed a pre-experimental method using a one-group pretest-posttest design. A total of 15 children were selected as participants through purposive sampling. Data collection techniques included tests, observation, and documentation. The data were analyzed using a one-sample t-test. The results of the t-test showed that t_count = 4.30 ≥ t_table = 1.761, indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. This finding suggests that ecoprint activities using the Belida fish pattern from South Sumatra have a significant effect on the fine motor development of children aged 5–6 years at RA Jamiyatul Qurro KH. Burlian, Ogan Komering Ulu.